2009
DOI: 10.1210/jc.2008-1180
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Via Steroidogenic Factor-1 Coordinately Regulates Transcription of Steroidogenic Genes Necessary for Estrogen Synthesis in Endometriosis

Abstract: Endometriotic cells contain the full complement of steroidogenic genes for de novo synthesis of estradiol from cholesterol, which is stimulated by PGE2 via enhanced binding of SF1 to promoters of StAR and aromatase genes in a synchronous fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(103 citation statements)
references
References 26 publications
5
95
0
3
Order By: Relevance
“…Recently, ERβ gain-of-function was shown to contribute to endometriotic lesion establishment and progression by evading the immune cell surveillance in mice (41). Furthermore, the inflammatory milieu of the disease, which is characterized by elevated PGE2, activates E2 synthesis in ectopic endometriotic stromal cells via SF1 and CYP19A1 activation (25, 36, 42, 43). In this study, we demonstrated that ERβ and PGE2 activate SGK1, leading to inhibition of pro-apoptotic factors that may support increased survival of endometriotic stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ERβ gain-of-function was shown to contribute to endometriotic lesion establishment and progression by evading the immune cell surveillance in mice (41). Furthermore, the inflammatory milieu of the disease, which is characterized by elevated PGE2, activates E2 synthesis in ectopic endometriotic stromal cells via SF1 and CYP19A1 activation (25, 36, 42, 43). In this study, we demonstrated that ERβ and PGE2 activate SGK1, leading to inhibition of pro-apoptotic factors that may support increased survival of endometriotic stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…181 Here, the COX-2-derived eicosanoid PGE 2 , as a potent inducer of aromatase and Steroidogenic acute regulatory protein expression, has a pivotal role. 182 Furthermore, estrogen degradation is regulated by progesterone and defective in progesterone resistance. 183 Estrogen may be pro-inflammatory in endometriosis 184 and contributes to the pathophysiology of the disease as a mitogen causing aberrant proliferation 185 and inhibition of apoptosis, 186 decreasing the tumor-suppressor phosphatase and tensin homolog deleted on chromosome 10 via NF-κB dependent pathways.…”
Section: Endometriosis: a Complex Disease For Which Improved Treatmenmentioning
confidence: 99%
“…STAR mRNA is reported to be expressed at low levels in ESCs but not in epithelial cells (Hukkanen et al 1998, Rhee et al 2003, Aghajanova et al 2009). However, STAR protein levels in total endometrial tissue homogenates detected by western blotting analysis were reported to be low to undetectable (Tsai et al 2001, Aghajanova et al 2009, Attar et al 2009), and to our knowledge, there are no studies reporting CYP11A1 or CYP17A1 protein expression or enzymatic activity in the endometrium. Androgen:oestrogen balance and regulation of the endometrial microenvironment.…”
Section: Androgen Biosynthesis and Expression Of Steroidmetabolisingmentioning
confidence: 81%